2010
DOI: 10.1021/jz101376m
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation on a Phospholipid Membrane Inducing a Characteristic Localization of DNA Accompanied by Its Structural Transition

Abstract: We report the coupling of phase separation on a phospholipid membrane with a structural transition of giant DNA. We performed single-DNA measurements in the presence of cell-sized giant unilamellar vesicles (GUV) composed of dioleoylphosphatidylcholine (DOPC), phosphatidylethanolamine (PE), and cholesterol. We observed the effect of phase separation of the membrane by changing PE from dioleoylphosphatidylethanolamine (DOPE) to dipalmitoylethanolamine (DPPE), which corresponds to a change from a homogeneous sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 31 publications
(59 reference statements)
2
36
0
Order By: Relevance
“…To avoid the intermolecular aggregation of T4 DNA molecules due to the addition of spermine, we perform experiments using a very low concentration of DNA (0.1-1.0 ng/mL). Consequently, encapsulated DNA molecules vary their conformations and spatial arrangements according to the concentrations of Mg 2þ and spermine, droplet size, and the types of lipid coating the droplet (Kato et al, , 2010. Figure 7.2 shows the distributions of T4 DNA labeled with the fluorescent dye YOYO-1 inside droplets with diameter <60 mm covered with two types of lipids: DOPE (dioleoylphosphatidylethanolamine) and DOPC.…”
Section: Preparation Of Dna and Actin Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid the intermolecular aggregation of T4 DNA molecules due to the addition of spermine, we perform experiments using a very low concentration of DNA (0.1-1.0 ng/mL). Consequently, encapsulated DNA molecules vary their conformations and spatial arrangements according to the concentrations of Mg 2þ and spermine, droplet size, and the types of lipid coating the droplet (Kato et al, , 2010. Figure 7.2 shows the distributions of T4 DNA labeled with the fluorescent dye YOYO-1 inside droplets with diameter <60 mm covered with two types of lipids: DOPE (dioleoylphosphatidylethanolamine) and DOPC.…”
Section: Preparation Of Dna and Actin Solutionmentioning
confidence: 99%
“…Such localization of DNA molecules on a DOPE membrane is confirmed using With a decrease in temperature, the ternary liposome separates into a DPPE-Chol-rich phase and a DOPC-rich phase. When we add DNA molecules exhibiting a compact conformation in aqueous solution, they are adsorbed onto the PE-rich phase in presence of the Mg 2þ by assuming an elongated conformation (Kato et al, 2010).…”
Section: Preparation Of Dna and Actin Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…We had to substitute bPS by ePE because incorporation of bPS interferes with the preparation of GUVs by the electroformation method (Rodriguez et al, 2000;Veatch and Keller, 2003), and thus we were not successful at producing GUVs with these mixtures. However, mixtures containing PE are used in a number of studies, for example, DPPE/DPPC (Bagatolli and Gratton, 2000a) or DMPE/ DMPC (Bagatolli and Gratton, 2000b), DMPC/DOPE/ PS (Perrier-Cornet et al, 2005), DOPC/DOPE/Chol, and DOPC/DPPE/Chol (Kato et al, 2010). In our ePEcontaining LUVs, the relative fraction of ePE showed a decreased value (g = 0.84) and increased values for Chol (g = 1.08) and eSM (g = 1.22).…”
Section: Luvs and Guvs Composed Of Ternary Mixturesmentioning
confidence: 99%
“…Their data demonstrated that efficiency of endocytosis was regulated by shape coupling between lipoplex and membrane lipids to suggest that such a shape-dependent coupling regulated efficient formation of endocytic vesicles thus determining the success of internalization (Marchini et al, 2010). Kato et al (Kato et al, 2010) observed the effect of phase separation of the membrane by changing PE from DOPE to dipalmitoylethanolamine (DPPE), which corresponded to a change from a homogeneous single phase to two segregated phases of liquid-ordered and liquid-disordered states on the membrane. This study further proved that helper lipids could change the morphologies of lipoplexes through the mutual interaction with DNA based on their chemical structures.…”
Section: Helper Lipids and Morphology Of Lipoplexesmentioning
confidence: 99%